Indoor performance analysis of URLLC service for industrial IoT. (5th October 2022) - Turk, Yekta
The ultra reliable low latency communication (URLLC) service consists of a great opportunity for mobile network operators (MNOs) for the industrial internet-of-things (IIoT) use cases. The URLLC service deployment requires careful considerations, and 100% service availability needs to be the ultimate goal across the factory area. However, it is critical to model the service availability for capacity analysis and observe performance tests for the URLLC service. In this article, the possible deployment scenarios for the URLLC service that can be provided in a factory environment are examined. Besides, a service availability model for URLLC is described. Afterwards, performance testing for realistic deployment scenarios that are based on time division duplex (TDD) is carried out. The results reveal that the framing structure of TDD has a direct impact on the capacity of URLLC, so that framing needs to be selected as a result of a careful site planning process.